The Impact of Promotional Strategies on Consumer Interest in Purchasing Toyota Innova Brand Cars at PT. Hadji Kalla, Sumoharjo Branch, Makassar City - Anur Achsanuddin UA; Muh. Nur R; Muhammad Ikram Idrus; Kahar Kahar (Jurnal Ilmu Manajemen Profitability, 2023)
This study aims to ascertain whether there exists a positive and significant impact of the Promotion Strategy on Consumer Interest in purchasing Toyota Innova cars at PT. Hadji Kalla's Sumoharjo Branch in Makassar City. The study encompasses two variables: the Promotion Strategy as the independent variable and Consumer Interest in purchasing a Toyota Innova as the dependent variable. The outcomes of the study reveal a simple linear regression equation as Y = 15.635 + 0.763X. The test results also yield a coefficient of determination (r) of 0.632, indicating that the Promotion Strategy influences Consumer Interest in Purchasing a Toyota Innova by 40%, while the remaining 60% is attributed to other factors not considered in this study. Moreover, the calculated t-value of 5.654 surpasses the t-critical value of 0.2353. This implies that the Promotion Strategy variable significantly and positively impacts consumer interest in purchasing a Toyota Innova. Thus, the hypothesis stands confirmed.